The Last Supper as a Convivium: The Ways of the Desacralization of Christian Images in Nether- landish Art of the First Half of the 16th Century - Kovbasiuk, Stefaniia A. (Actual Problems of Theory and History of Art, 2016)
In this article, we aspire to explore the peculiar ways of desacralization in Netherlandish Art of the first half of the 16th century through the example of the Last Supper images. By “desacralization” in this case (the period up to 1566), we mean not only the process of full depreciation of sacred images, but the manifested before the iconoclastic uprising tendency to introduce some uncanonical details, which changed essentially the mode of the representation. Amongst the first artists to depict the Last Supper in the 16th century were the painters from the group of so-called “Antwerp Mannerists”. As early as in the earliest examples of the 1515–1520s, the Last Supper is depicted as a convivium — a profane feast.The most noticeable feature of “desacralization” in the iconography of the Last Supper became the so- called “detail with a knife” — the image of an Apostle picking his teeth with a knife during the last meal of Jesus with His disciples. In some depictions of the Last Supper, this scene was complemented with the image of another disciple gnawing a bone. These details show changes in the ideological sphere which concerned the concept of sanctity, as well as the threshold of permissible in the sacred images. The desacralization of Christian images in Netherlandish art of the first half of the 16th century occurred in the first place by means of depicting the Apostles as “mere mortals” with all their imperfections.